732. Microbiologic and clinical outcome concordance in the global phase 3 ATTACK trial: Sulbactam-durlobactam (SUL-DUR) versus colistin therapy in patients with Acinetobacter baumannii-calcoaceticus complex (ABC) infections. (15th December 2022) - Altarac, David; Miller, Alita; McLeod, Sarah; Shapiro, Adam B; Rana, Khurram; Lewis, Drew; Poirier, Gabrielle; Chabas, Daria
Abstract: Background: SUL-DUR is a β-lactam/β-lactamase inhibitor combination in development for the treatment of ABC, which is a cause of severe infections with substantial mortality. ATTACK evaluated the efficacy and safety of SUL-DUR versus colistin (COL) in patients with serious ABC infections. Methods: Part A was a randomized, blinded non-inferiority study (SUL-DUR versus COL) in ABC pneumonia or bacteremia; Part B was an open label study (SUL-DUR only) that enrolled patients with ABC infections who did not tolerate COL or whose pathogens were resistant to COL (COL-R). All subjects received imipenem/cilastatin as background therapy. Primary endpoint included 28-day all-cause mortality (ACM) in Part A patients with carbapenem-resistant ABC at baseline (CRABC m-MITT). Clinical and microbiologic outcomes were measured at the End of Therapy (EOT), Test of Cure (TOC) and Late Follow-up (LFU) visits in CRABC m-MITT patients. In this study, COL-R was defined as MIC ≥ 4 µg/ml and SUL-DUR-non-susceptible (NS) was defined as MIC ≥ 8 µg/ml. Results: SUL-DUR was non-inferior to COL in 28-day ACM; 19.0% SUL-DUR versus 32.3% in the COL group (Table 1). SUL-DUR therapy resulted in statistically significant higher clinical cures at EOT and TOC. Similarly, a significant treatment difference in microbiological favorable assessment was observed at EOT and TOC (24.4% and 26.3%, respectively, in Part A). Similar mortality differences were observed in subgroups including infection type, severity of illness, mechanical ventilation, and duration of stay of at least 5 days in the ICU prior to starting study treatment (Table 2). All 149 baseline ABC isolates from CRABC m-MITT patients were multi-drug resistant; the SUL-DUR MIC50/90 was 2/4 µg/ml (range of 0.25 – 8 µg/ml). At baseline 33% of ABC infections were polymicrobial. Conclusion: In ATTACK, patients treated with SUL-DUR had lower mortality, higher clinical cure rates and significantly greater microbiologically favorable outcomes than those treated with COL. The correlation between clinical and microbiologic outcomes provides additional evidence that, if approved, SUL-DUR could be an important therapeutic option for Acinetobacter infections including carbapenem-resistant and multidrug-resistant strains. Disclosures: David Altarac, MD, MPA, Entasis Therapeutics: Ownership Interest|Entasis Therapeutics: Stocks/Bonds Alita Miller, PhD, Entasis Therapeutics: Employee Sarah McLeod, PhD, Entasis Therapeutics: Employee Adam B. Shapiro, Ph.D, Entasis Therapeutics: Employee|Entasis Therapeutics: Stocks/Bonds Khurram Rana, PharmD, Entasis Therapeutics: Employee|Entasis Therapeutics: Ownership Interest|Entasis Therapeutics: Stocks/Bonds Drew Lewis, MD, MTM&H, Entasis Therapeutics: employee|Entasis Therapeutics: employee|Entasis Therapeutics: Stocks/Bonds|Entasis Therapeutics: Stocks/Bonds Gabrielle Poirier, BS, Entasis Therapeutics: Ownership Interest|Entasis Therapeutics: Stocks/Bonds Daria Chabas, BS, Entasis Therapeutics: Ownership Interest|Entasis Therapeutics: Stocks/Bonds.